Thermal biology of Lanthanotus borneensis (Lanthanotidae) in Sarawak, Borneo - Veronica, Leah; Pui, Yong Min; Indraneil, Das (Koninklijke Brill NV, 2023)
Lanthanotus borneensis, the Bornean earless monitor, is a monotypic member of the family Lanthanotidae, and restricted to the island of Borneo. Little has been published on its field ecology. This study investigated aspects of its thermal biology through an analysis of surface body temperatures of free ranging individuals against corresponding environmental temperatures, in order to explore aspects of microhabitat utilisation in relation to thermoregulation. A generalised linear mixed model shows significant effect of air and substrate temperatures, but not of water temperature. Further, the fixed effects of substrate temperature (coefficient estimate 0.396; P < 0.05) versus ambient temperature (0.264; P < 0.05), is suggestive of thigmothermy as the primary mode of thermoregulation. The species does not appear to utilise specific microhabitat structures to thermoregulate, the results of these observations suggesting that it is a thermoconformer.